SOCIAL CONSTRUCTION OF TEACHER STRESS AND ITS REFLECTIONS IN OCCUPATIONAL PRESS - Bubelienė, Daiva; Merkys, Gediminas (Acta Paedagogica Vilnensia, 2012)
The article presents an analysis of the discourse of teacher occupational periodicals on teacher stress, its effects and contexts of expression. Public opinion about the prestige of the teaching profession, workload, teacher’s health, school microclimate, etc. is formed by the political and social interests of different actors represented in the media. A piece of the scientific information obtained during a research project on occupational stress in Lithuanian teachers has been employed in the study (Bubelienė, 2010; Bubelienė, Merkys, 2010; Merkys, Bubelienė, 2009). The analysis of the professional press discourse is aimed at revealing how various actors introduce socially constructed worldviews, values, ideas, attitudes, and opinions, and give a sense to situations, social roles, identities, and interpersonal relationships in the process of discourse. Occupational factors, contexts and sources of risk leading to an increased occupational stress in teachers are examined. The article presents the results of the research and the emerged thematic plot lines that reflect the determinants of the teacher stress at macro, organizational, and micro levels. The analysis of the teacher professional press discourse has shown that the topic of the teacher stress in the Lithuanian public discourse and public opinion occupies a position of a comparatively high relevance in terms of numerous stress determinants and contexts. It has been revealed that the discourse on occupational stress in teachers mainly reflects the social factors on the macro level, which have a substantial effect on the expression of occupational stress in teachers.